2011
DOI: 10.1074/jbc.m111.284729
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Regulation of Dopamine after Ablation of the Tyrosine Hydroxylase Gene in the Nigrostriatal Projection

Abstract: Background:The tyrosine hydroxylase (TH) gene, essential for dopamine synthesis, is partially ablated in adult nigrostriatal projection. Results: TH reduction in axon terminals is slower than in soma, and dopamine is better maintained than TH. Conclusion: Striatal dopamine is compensatorily regulated by axonal TH level and L-DOPA synthesis activity per TH level. Significance: This regulation has potential relevance to pathogenesis of Parkinson disease and other dopamine-related psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
5
16
0
Order By: Relevance
“…Our results along with reports of Cre toxicity in transgenic mice emphasize the importance of appropriate controls for Cre effects, seldom included in studies implicating Cremediated recombination. AAV-mediated Cre recombination is a common method to study gene function in the brain, including in the SN (Tokuoka et al 2011;Yu et al 2012), with viral titers often comparable to those used in our study (Yu et al 2012;Yeo and Herbison 2014;Shen et al 2016;Kopra et al 2017), but the local effects of Cre expression have been poorly investigated. Maintaining an appropriate balance between recombination of the target gene and toxicity is an important pitfall in studies using Cre recombinase.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our results along with reports of Cre toxicity in transgenic mice emphasize the importance of appropriate controls for Cre effects, seldom included in studies implicating Cremediated recombination. AAV-mediated Cre recombination is a common method to study gene function in the brain, including in the SN (Tokuoka et al 2011;Yu et al 2012), with viral titers often comparable to those used in our study (Yu et al 2012;Yeo and Herbison 2014;Shen et al 2016;Kopra et al 2017), but the local effects of Cre expression have been poorly investigated. Maintaining an appropriate balance between recombination of the target gene and toxicity is an important pitfall in studies using Cre recombinase.…”
Section: Discussionmentioning
confidence: 65%
“…AAV‐mediated Cre recombination is a common method to study gene function in the brain, including in the SN (Tokuoka et al . ; Yu et al . ), with viral titers often comparable to those used in our study (Yu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that there are compensatory mechanisms that have yet to be explained in Jam-b-deficient animals; however, these were not evident in our aortic explant studies where an effect was observed. Such compensatory mechanisms have been showninotherdiseasemodels-for example, in the mouse brain when tyrosine hydrolase is inactivated (61) or in prostate cancer cell lines when Bcl-2 is down-regulated (62). Another hypothesis is that JAM-B could be necessary for inflammatory angiogenesis (63) (64) rather that tumor angiogenesis.…”
Section: In Vivo Jam-b Targeting Does Not Impact On Tumor Developmentmentioning
confidence: 98%
“…In a recent study, ablation of the TH gene in mice revealed that TH protein levels in the axon terminals are regulated differently from that in the soma, and that tissue dopamine levels are under trans-axonal compensatory regulation: The reduction of dopamine in some axons induces enhanced dopamine synthesis in others (Tokuoka et al, 2011). Trans-axonal compensation may be mediated by phsophorylation of TH, decreased dopamine reuptake or by neurotrophic factors.…”
Section: Compensatory Mechanisms In Presymptomatic and Early Pd Diseasementioning
confidence: 99%